1985
DOI: 10.1002/recl.19851040103
|View full text |Cite
|
Sign up to set email alerts
|

The influence of substituents on the geometry of the cyclopropane ring. I. The crystal and molecular structure of cyanocyclopropane at −85°C. Film and diffractometer measurements

Abstract: Abstract. Crystals of cyanocyclopropane have been grown from liquid. At -85"C, cell parameters are a = 7.244(5), b = 7.821(2), c = 6.916(3) 8, in the orthorhombic space group Pnma with Z = 4. Intensity data were collected in three different ways, viz. photographically using rotation and Weissenberg techniques and electronically by means of a diffractometer. Within the limits of accuracy, the three data sets result in equal bond lengths and angles. The most important result from the structure determination is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A second test concerned the powderdiffractogram of CPCN (Kiers, de Boer, Heijdenrijk, Stam and Schenk, 1985) generated from single-crystal data (Jansen, Peschar and Schenk, 1992a). It was shown that many of the normalized structure-factors, obtained by the least-squares fitting procedure LSQPROF, which were indicated to be strong or weak, are not strong respectively weak at all (Jansen, Peschar and Schenk, 1992b).…”
Section: Preliminary Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A second test concerned the powderdiffractogram of CPCN (Kiers, de Boer, Heijdenrijk, Stam and Schenk, 1985) generated from single-crystal data (Jansen, Peschar and Schenk, 1992a). It was shown that many of the normalized structure-factors, obtained by the least-squares fitting procedure LSQPROF, which were indicated to be strong or weak, are not strong respectively weak at all (Jansen, Peschar and Schenk, 1992b).…”
Section: Preliminary Test Resultsmentioning
confidence: 99%
“…Figure 1 shows the differences of the fitted and true normalized structure factors of CPCN (Kiers, de Boer, Heijdenrijk, Stam and Schenk, 1985) after the application of the Direct Intensity Fitting technique as a function of the interpeak distance in units of the halfwidth of the peaks. It can be seen that the intensities become less reliable if the interpeak distance decreases.…”
Section: Weighting Scheme For Intensitiesmentioning
confidence: 99%
“…In addition to their ability to interact with adjacent π systems, cyclopropanes function as effective donors when activated by adjacent low‐lying empty orbitals: this can be rationalized by considering the Walsh orbitals 6. 7 Striking manifestations of the electron‐donating aptitude of cyclopropanes include: 1) the unusual thermodynamic stability of the cyclopropylcarbinyl cation,8 and 2) the bond‐length asymmetry of cyclopropanecarbonitirile (Δd (distal−vicinal) =0.033 Å) as a consequence of hyperconjugation 9. 10 Of particular pertinence to this study is the latter observation.…”
Section: Methodsmentioning
confidence: 92%